GUESTBOOK SYSTEM FOR LABORATORY SECRETARIAT DURING COVID-19 PANDEMIC - Noor Falih; Sarika Sarika; Artika Arista (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2021)
“Go Green Campus” is a university program that requires all elements on campus to minimize the use and waste of paper and plastic. This encourages the transition from paper data collection to digitizing data storage to computer media. The Guest Book web application for Secretariat Lab of Faculty of Computer Science (FIK) Universitas Pembangunan Nasional Veterans Jakarta (UPNVJ) is a website-based software to facilitate the process of collecting visitor’s data who visit the FIK lab secretariat room. This application can replace the previous conventional guestbook to digital. The application built using the waterfall method and using the PHP programming language with the Laravel framework and MySQL database running on a local server. The Guestbook Web-based system for the Secretariat of the Laboratory of the FIK, UPNVJ can gather student’s data who visit the FIK lab secretariat room and the information can be downloaded in pdf and excel form. This web application also provides features such as covid-19 self-screening survey, news information, critics and suggestions, and the activity log list. The system that has been developed has also passed the security aspect test, reliability aspect test, portability aspect test, usage aspect test and is able to carry out the designed process.